PENGARUH PERLINDUNGAN INVESTOR TERHADAP HUBUNGAN ANTARA KECAKAPAN MANAJERIAL DAN MANAJEMEN LABA - , FAJAR RINA SEJATI, Prof. Dr. Indra Wijaya Kususma, MBA., CMA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Managerial ability were positively related to earnings management (Isnugrahadi and Kusuma, 2009). More able managers will be easier to manage earnings management, both discretionary accruals and real earnings management (Demerjian et al. 2012b). The level of investor protection becomes one of the external factors that can reduce the occurrence of earnings management (Leuz et al., 2003). The high protection afforded to investors could be expected to reduce earnings management is carried out by able manager. Assuming opportunistic earnings management, so that a more able manager will be easier to manage earnings management, the assumption is proved by regression analysis conducted on manufacturing firms in six (6) countries in Asia, namely Indonesia, Japan, South Korea, Malaysia, Singapore, and Thailand (from the OSIRIS database) in 2010-2013. Managerial ability were measured using enterprise efficiency score, earnings management is proxied by discretionary accruals and real earnings management, as well as investor protection is measured using five dimensions derived from the World Economic Forum. With 95 percent confidence level, the findings of this study support previous findings that managerial ability significant positively related to earnings management, both for discretionary accrual and real earnings management. However, this study only found that there are interaction effects between managerial ability and the investor protection to influence managerial ability on earnings management, as well as empirical results on the analysis of this study, for real earnings management. Meanwhile, for the discretionary accrual, there were no interaction effects between managerial ability and investor protection to influence managerial ability to earnings management. The level of investor protection plays a role in mitigating a significant positive effect of managerial ability on earnings management, for real earnings management.